2002
DOI: 10.1074/jbc.m111546200
|View full text |Cite
|
Sign up to set email alerts
|

Folding of Dimeric Methionine Adenosyltransferase III

Abstract: Methionine adenosyl transferase (MAT) is an essential enzyme that synthesizes AdoMet. The liver-specific MAT isoform, MAT III, is a homodimer of a 43.7-kDa subunit that organizes in three nonsequential ␣-␤ domains. Although MAT III structure has been recently resolved, little is known about its folding mechanism. Equilibrium unfolding and refolding of MAT III, and the monomeric mutant R265H, have been monitored using different physical parameters. Tryptophanyl fluorescence showed a three-state folding mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(34 citation statements)
references
References 38 publications
(29 reference statements)
1
33
0
Order By: Relevance
“…Thus, in this denaturant range the SS alterations take place together with the largest changes in the tryptophan environment, leading to a monomeric intermediate (J), which is the species detected by sedimentation velocity and that is prone to aggregation according to the gel filtration results. All these results together suggest multi-state denaturation for Mj-MAT, although the number and association state of the intermediates differs from those of MAT III and BsMAT [11,12,23]. Furthermore, MATs also differ in the polar character of their intermediates as judged from their ANS binding capacities.…”
Section: Resultsmentioning
confidence: 86%
See 3 more Smart Citations
“…Thus, in this denaturant range the SS alterations take place together with the largest changes in the tryptophan environment, leading to a monomeric intermediate (J), which is the species detected by sedimentation velocity and that is prone to aggregation according to the gel filtration results. All these results together suggest multi-state denaturation for Mj-MAT, although the number and association state of the intermediates differs from those of MAT III and BsMAT [11,12,23]. Furthermore, MATs also differ in the polar character of their intermediates as judged from their ANS binding capacities.…”
Section: Resultsmentioning
confidence: 86%
“…These data suggest incomplete unfolding of Mj-MAT even at the highest urea concentration tested, although monomer production is obtained according to the s 20,w value. Comparison with the available data for other members of the MAT family revealed that mesophilic isoenzymes, MAT III [11,12] and BsMAT [23], show complete loss of CD signature and total red-shift of their λ max at 8M urea. Moreover, Mj-MAT retains activity even in 6 M urea, whereas complete loss of AdoMet synthesis and PPP i hydrolysis was already observed at 1 M urea with MAT III [11,12] and BsMAT [23].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although all three MAT forms share 85% of the aminoacidic sequence [18,19], they differ in their kinetic and regulatory properties [14]. While MATI/III are activated by the substrates methionine and ATP [20], MATII is inhibited by the product of the reaction, SAM [17]. Consistently, cells expressing MAT1A have higher SAM levels than cells expressing MAT2A [21].…”
Section: Introductionmentioning
confidence: 99%